Factores de riesgo y estado nutricional de los estudiantes de primer y segundo grado de la I.E.P.M. N°60039 Tamshiyacu 2019 - Lopez Cobos, Anita Rubi (2021)
The present investigation was to determine the risk factors involved in the nutritional status of first and second grade children of the I.E.P.M N ° 60039 Tamshiyacu. The research is non-experimental, descriptive, correlational, cross-sectional; the sample was of 144 schoolchildren; Instruments such as a food consumption frequency survey were used; nutritional evaluation file, physical activity survey, and socio-economic level survey; nutritional status was determined by BMI / E, T / E. It was found that 76% have normal height / age, 14% short height, and 10% tall height, likewise 60% have a normal BMI / Age, 23% are overweight, and 17% are obese; 15% present unhealthy habits, 44% adequate or sufficient, and 41% healthy habits; 10% of those evaluated have a low frequency of food consumption, 24% average, and 66% a high consumption of healthy foods; for physical activity, 1% have a high level, 38% a normal level, 60% a low level, and 2% a very low level; 47% of those evaluated have a low socioeconomic level, 36% a medium level, and 16% a high level; There is a positive relationship of very low height / age level and eating habits, frequency of food consumption, physical activity and socio-economic level with a value of bilateral significance (p = 0.02; 0.041; 0.029; and 0.046) with Rho Spearman's (0.253, 0.066, 0.117 and 0.086); Likewise, there is a positive relationship of very low level of BMI / Age and eating habits, frequency of food consumption, level of physical activity, and socioeconomic level, with a confidence level of 95%, it is said, that for height / age and eating habits, frequency of food consumption, physical activity, and socioeconomic level with value of bilateral significance (p = 0.031, 0.044, 0.012, and 0.018) with Spearman's Rho (0.129, 0.121, 0.278 and 0.120).